Contrasting confocal with defocusing microscale spatially offset Raman spectroscopy. (11th December 2015) - Conti, C.; Realini, M.; Colombo, C.; Botteon, A.; Matousek, P.
Abstract : The study compares and contrasts conventional confocal Raman microscopy/spectroscopy (CRM) with a recently developed micrometer scale defocusing spatially offset Raman spectroscopy (micro‐SORS), a method providing a new analytical capability for investigating non‐destructively the chemical composition of subsurface, micrometer‐scale‐thick diffusely scattering layers at depths beyond the reach of CRM. Because of close similarities between the two techniques and comparable embodiment of the instrumentations, but radically different interpretations of data, it is crucially important to recognise which type of method is pertinent to a specific measurement. The distinction comes principally from the nature of sample, whether turbid (micro‐SORS measurement) or transparent (CRM measurement) on the spatial scale of the axial (z‐)scan of the measurement. Which type of sample one deals with may not always be easily recognisable with micro‐scale thick layers, and the study therefore also presents a simple method for suggesting whether CRM or micro‐SORS methodology applies. This test relies on an axial (z‐)scan performed through the sample in both the positive and negative directions from the normal, imaged sample surface position using conventional CRM instrument. The absence or presence of symmetry or asymmetry of the intensity profiles of measured Raman signals around the imaged sample surface position as a function of sample axial displacement then suggests which interpretation could apply. The study paves a way for the development of micro‐SORS as a widely applicable analytical tool deployable on conventional Raman microscopes. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The study compares and contrasts confocal Raman microscopy with micro‐scale defocusing spatially offset Raman spectroscopy, a recently developed method providing a new analytical capability for investigating non‐destructively the chemical composition of subsurface, micrometer‐scale‐thick diffusely scattering layers at depths beyond the reach of confocal Raman microscopy.